Helms-Burton law : development, consequences, and legacy for inter-American and European-US relations. - ROY, Joaquin (1997)
Traces the evolution and consequences of the Helms-Burton law in relation to the objectives of the US and the major sources of international opposition : the European Union (especially Spain), Canada, and Mexico.